Criminal offences against the binding rules of a market economy : Violation of competition rules - Saparová, Katarína (2025)
This thesis examines the criminal-law regulation of the most serious infringements of competition rules under section 248 of the Czech Criminal Code, focusing on the material and formal elements of the offence and on the boundary between administrative and criminal enforcement of cartel conduct. Special attention is devoted to the impact of digitalisation on the formation and detection of cartels, particularly algorithmic coordination, the absence of traditional evidence, and the increasing need for forensic and technical investigative tools. The thesis shows that administrative enforcement remains the primary mechanism for protecting competition, while criminal liability operates as an ultima ratio instrument applicable only in cases of serious intentional conduct resulting in significant harm or unlawful gain. It also assesses the effectiveness of leniency programmes and formulates recommendations to enhance cooperation between the Czech Competition Authority and criminal enforcement bodies, including improved use of state data sources and modern analytical methods. The findings contribute to understanding the limits of criminalising cartel conduct in a digitalised economy.